2012
DOI: 10.4103/0976-237x.101092
|View full text |Cite
|
Sign up to set email alerts
|

Caries infiltration of noncavitated white spot lesions: A novel approach for immediate esthetic improvement

Abstract: The earliest evidence of demineralization on the smooth enamel surface of a crown is a white spot lesion. The conventional treatment of these white spot lesions includes topical fluoride application, iamproving the oral hygiene, and use of remineralizing agents. The following article illustrates the use of a novel approach to treat smooth surface noncavitated white spot lesions microinvasively based on infiltration of enamel caries with low-viscosity light curing resins called infiltrants. This treatment aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 7 publications
2
57
0
12
Order By: Relevance
“…The effect of lesion progression as seen in approximal lesions was confirmed for labial lesions, also (34,36) . Furthermore, case reports and short-term studies (9,32,34,35,(37)(38)(39)(40)(41)(42)(43)(44)(45) describe a masking of WSL, up until 1 year following infiltration (32,37,46) . Hammad et al distinguished between infiltration of visible WSLs without surface disruption and WSLs with a roughened surface not requiring restoration, and reported significant improvement in both groups following infiltration.…”
Section: Post-orthodontic Wsl In Vivomentioning
confidence: 99%
“…The effect of lesion progression as seen in approximal lesions was confirmed for labial lesions, also (34,36) . Furthermore, case reports and short-term studies (9,32,34,35,(37)(38)(39)(40)(41)(42)(43)(44)(45) describe a masking of WSL, up until 1 year following infiltration (32,37,46) . Hammad et al distinguished between infiltration of visible WSLs without surface disruption and WSLs with a roughened surface not requiring restoration, and reported significant improvement in both groups following infiltration.…”
Section: Post-orthodontic Wsl In Vivomentioning
confidence: 99%
“…Según algunos reportes el tratamiento de caries incipientes con resinas infiltrantes ha demostrado ser una opción viable tanto "in vitro" como "in vivo", ya que aumentarían la Microdureza superficial de éstas y conseguirían un sellado de las microporosidades del esmalte subsuperficial, evitando así la progresión de la lesión (8)(9)(10)(11)(12).…”
Section: Discussionunclassified
“…WSLs in enamel are of major interest because they represent the first stage of a carious lesion. These classical areas of WSL lose their translucency because of the extensive subsurface porosity caused by demineralization and should be distinguished from developmental white spot hypocalcifications of enamel [3]. Boersma et al investigated the prevalence of white spot lesions (WSL) at the end of orthodontic treatment by using the QLF (Quantitative Light-induced Fluorescence) technique and found that 97% of the subjects had one or more lesions [4].…”
Section: Introductionmentioning
confidence: 98%